Reconstruction of The Information Technology-Based Cybercrime Prevention Model in The National Cyber Law System - Erlan Bachtiar; Ernawati, Ninin (Journal of Law and Policy Transformation, 2025)
The increasingly complex development of information technology has increased the frequency and variety of cybercrime in Indonesia. Although the national legal framework, particularly Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), has provided a legal basis for combating cybercrime, effective prevention still faces challenges. These challenges include a lack of synchronized norms, limited early detection mechanisms, low system interoperability, and slow policy updates compared to the rapid evolution of cybercrime methods. This study aims to analyze the weaknesses of the current prevention model in the national cyber law system and formulate a reconstruction of a more adaptive, responsive, and technology-based cybercrime prevention model oriented toward strengthening cyber resilience. Using a juridical-normative approach, this study examines laws and regulations, court decisions, and international information security standards. The analysis results indicate the need for an integrated prevention model that includes: an AI-powered threat intelligence-based early detection system and cross-sectoral regulatory harmonization. This model reconstruction is expected to serve as a foundation for updating national cyber law policies to be more effective in addressing the dynamics of cyber threats in the digital era.